Activated carbon electrode materials
Patent Information
- Application Number
- JP2021526429
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-13
- Filing Date
- 2019-11-12
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2039-11-12
Smart Images

Figure 0007652391000002 
Figure 0007652391000003 
Figure 0007652391000004
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Prov. Pat. App. No. 62 / 760,730, filed November 13, 2018, the entire contents of which are incorporated herein by reference.
[0002] Technical Field The present invention relates to electrode materials for energy storage devices. More specifically, the present invention relates to activated carbon materials for use as electrode materials in energy storage devices, such as batteries and supercapacitors.
[0003] Summary of the Invention One embodiment of the present invention is an activated carbon powder comprising activated carbon particles, the activated carbon particles having a diameter of about 900 mm. 2 / g ~ approx. 2,500m 2 The activated carbon powder has a Brunauer-Emmett-Teller (BET) surface area in the range of 1 / g. (a) Below: (i) sp 3 D-band carbon, which corresponds to a hybrid disordered carbon phase, and (ii) sp 2 G-band carbon corresponding to a hybrid graphite phase Including carbon, Here, the D band carbon and the G band carbon are identified using Raman spectroscopy, and the D band carbon (I D ) and G-band carbon (I G ) is the relative intensity of I G / I D The ratio is in the range of 0 to about 2. (b) nitrogen in an amount ranging from about 0.3 atomic % to about 1.8 atomic % of the activated carbon particles, as determined by X-ray photoelectron spectroscopy; wherein at least some of the nitrogen atoms are sp 2Substituting carbon atoms in the crystal lattice structure of the hybrid graphite phase, (c) Diameter 2nm~ 50 Mesopores with diameters in the nm range and micropores with diameters below 2 nm The activated carbon particles include (i) average pore width as determined by the Barrett-Joyner-Halenda (BJH) method: in the range of about 1 nm to about 4 nm; (ii) Micropore surface area determined by t-plot method: approx. 300 m 2 / g ~ approx. 1,350m 2 / g range, and (iii) Cumulative surface area of micropores with hydraulic radii in the range of 0.285 nm to 1.30 nm: approx. 1,000 m 2 / g ~ approx. 3,000m 2 / g range has.
[0004] One embodiment of the present invention relates to a method for producing the above-mentioned activated carbon particles of the activated carbon powder, the method comprising the steps of: performing an activated pyrolysis treatment of a precursor comprising powder of uncarbonized plant material, powder of partially carbonized plant material, or a combination thereof; Here, the activated pyrolysis treatment is - mixing the precursor with an activator to form a precursor and activator mixture; wherein the activating agent is selected to react with carbon in the precursor during the activation pyrolysis process to form one or more products suitable for removal during a cleaning process carried out after the activation pyrolysis process, and combinations thereof; and - heating the mixture of precursor and activator under an inert pyrolysis atmosphere at a pyrolysis temperature and for a pyrolysis time sufficient to complete carbonization of the precursor to form an activated pyrolyzed material; Including, and, performing a washing treatment of the activated pyrolysis material with one or more washing solutions suitable for reducing or removing one or more products of the reaction between the carbon and the activating agent from the activated pyrolysis material to form activated carbon particles of the activated carbon powder; Includes.
[0005] One embodiment of the present invention relates to an electrode comprising the activated carbon powder described above.
[0006] One embodiment of the present invention relates to a battery comprising the electrode described above.
[0007] One embodiment of the present invention relates to a supercapacitor comprising the above-described electrode. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 includes a graph showing the specific capacitance of a commercial carbon and an activated carbon according to an embodiment of the present invention as a function of sweep rate and current density. [Diagram 2] FIG. 2 includes XRD patterns of carbon derived from soybean leaves at leaf:KOH mass ratios of 1:0 (unactivated), 1:0.5, 1:1, and 1:2. [Diagram 3] FIG. 3 contains nitrogen adsorption-desorption isotherms for soybean leaf derived carbon activated with leaf:KOH mass ratios of 1:0.5, 1:1, and 1:2. [Figure 4] FIG. 4 contains plots of the BJH pore size distribution of activated carbons derived from soybean leaves activated with leaf:KOH mass ratios of 1:0.5, 1:1, and 1:2. [Diagram 5] FIG. 5 contains Raman spectra of carbon derived from soybean hull material activated with hull:KOH mass ratios of 1:0.5, 1:1, 1:2, and 1:3. [Figure 6] FIG. 6 contains Raman spectra of carbon derived from soybean stalk material activated with stalk:KOH mass ratios of 1:0.5, 1:1, 1:2, and 1:3. [Figure 7]FIG. 7 includes Raman spectra of carbon derived from soybean leaf material activated with leaf:KOH mass ratios of 1:0 (unactivated), 1:0.5, 1:1, and 1:2. [Figure 8] FIG. 8 contains scanning electron microscope (SEM) images of carbon derived from soybean hull, stem and leaf material activated at the indicated soybean material:KOH mass ratios. [Figure 9] Figure 9 encompasses the XRD patterns of carbon derived from soybean husks activated with husk:KOH mass ratios of 1:0 (unactivated, SB-husk-1), 1:0.5 (SB-husk-2), 1:1 (SB-husk-3), 1:2 (SB-husk-4), and 1:3 (SB-husk-5). [Figure 10] Figure 10 encompasses the XRD patterns of carbon derived from soybean stalks activated with stem:KOH mass ratios of 1:0 (unactivated, SB-stem-1), 1:0.5 (SB-stem-2), 1:1 (SB-stem-3), 1:2 (SB-stem-4), and 1:3 (SB-stem-5). [Figure 11] FIG. 11 contains the nitrogen adsorption-desorption isotherms of carbon derived from activated soybean husks with husk:KOH mass ratios of 1:0 (unactivated, SB-husk-1), 1:0.5 (SB-husk-2), 1:1 (SB-husk-3), 1:2 (SB-husk-4), and 1:3 (SB-husk-5). [Figure 12] FIG. 12 contains the nitrogen adsorption-desorption isotherms of carbon derived from soybean stalk activated with stalk:KOH mass ratios of 1:0 (unactivated, SB-stalk-1), 1:0.5 (SB-stalk-2), 1:1 (SB-stalk-3), 1:2 (SB-stalk-4), and 1:3 (SB-stalk-5). [Figure 13] FIG. 13 contains plots of the BJH fine size distribution of activated carbons derived from soybean husks activated with husk:KOH mass ratios of 1:0 (unactivated, SB-husk-1), 1:0.5 (SB-husk-2), 1:1 (SB-husk-3), 1:2 (SB-husk-4), and 1:3 (SB-husk-5). [Figure 14]FIG. 14 contains plots of the BJH pore size distribution of activated carbons derived from soybean stalk activated with stem:KOH mass ratios of 1:0.5 (SB-stem-2), 1:1 (SB-stem-3), 1:2 (SB-stem-4), and 1:3 (SB-stem-5). [Figure 15] FIG. 15 shows the change in specific capacitance of sample SB-husk-3 (i.e., activated carbon derived from soybean husks with a 1:1 mass ratio of husks:KOH) in various electrolytes as a function of applied current density. [Figure 16] FIG. 16 shows the charge / discharge profiles of commercial carbon and nitrogen-doped commercial carbon. [Figure 17] FIG. 17 is a graph of the % capacitance retention and coulombic efficiency as a function of the number of charge-discharge cycles for a coin cell supercapacitor fabricated using an activated carbon material of one embodiment of the present invention. [Figure 18] FIG. 18 is a graph comparing the CV curves at 100 mV / sec of activated carbons produced from soybean stalk using the two-stage method and activated using a 1:0.5 mass ratio with the CV curves at 100 mV / sec of activated carbons produced using the one-stage method and activated using a 1:0.5 mass ratio. [Figure 19] FIG. 19 is a graph comparing the CV curves at 200 mV / sec for activated carbons produced from soybean stalk using the two-stage method and activated using a 1:0.5 mass ratio with the CV curves at 200 mV / sec for activated carbons produced using the one-stage method and activated using a 1:0.5 mass ratio. [Figure 20] FIG. 20 is a graph comparing the charge storage capacity at 1 A / g of activated carbon produced from soybean stalk using a two-stage process and activated carbon produced using a one-stage process, where the ratios shown above each bar are the pre-activated carbon:activator ratio for the two-stage process and the soybean stalk:activator ratio for the one-stage process. [Figure 21]FIG. 21 is a graph comparing the charge storage capacity at 5 A / g of activated carbon produced from soybean stalk using a two-stage process and activated carbon produced using a one-stage process, where the ratio shown above each bar is the pre-activated carbon:activator ratio for the two-stage process and the soybean stalk:activator ratio for the one-stage process. [Figure 22] FIG. 22 is a graph comparing the rate characteristics of charge storage capacity at three current densities (1 A / g, 5 A / g, and 10 A / g) of soybean stalk-based activated carbon (1:0.5) synthesized using the one-step method. [Diagram 23] FIG. 23 is a graph showing (A) the charge storage capacity as a function of applied current density and (B) the power density as a function of energy density in 6 M KOH electrolyte for devices fabricated using the one-step method with activated carbon in stem:KOH (1:1). [Figure 24] FIG. 24 is a graph showing (A) capacitance retention and coulombic efficiency as a function of charge / discharge cycles for devices using soybean stalk:KOH (1:1) activated carbon fabricated using a one-step method, and (B) charge / discharge characteristics of device 1, devices 1 and 2 connected in series, and devices 1, 2, and 3 fabricated in series, each of which was fabricated using carbon synthesized in a one-step using soybean stalk:KOH (1:1) activated carbon, and where device 1 utilized 6M KOH as the electrolyte, device 2 utilized 6M NaOH as the electrolyte, and device 3 utilized 6M LiOH as the electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Detailed Description of the Invention I. Activated carbon powder containing activated carbon particles As indicated above, one embodiment of the present invention relates to an activated carbon powder comprising activated carbon particles. Importantly, the activated carbon particles of the present invention are derived from plant-based materials that are typically considered waste. As discussed in more detail below, it is believed that the composition of the starting material, together with the processing of said material, results in activated carbon particles with desirable properties compared to those of commercially available carbon particles. For example, one embodiment of the activated carbon particles of the present invention, thanks to the activated carbon of said embodiment, was observed to exhibit about 7.5 times the energy storage capacity and stable rate performance of commercially available carbon electrode materials, maintaining about 83% of its initial storage capacity when increasing the discharge current density from 3 A / g to 15 A / g, while the commercially available carbon particles maintained only about 16% of its initial storage capacity under similar conditions.
[0010] II. Manufacturing method of activated carbon particles A. Plant-Based Materials As mentioned above, the activated carbon particles of the present invention are derived from plant-based materials. Essentially any suitable plant-based material can be used, but for economic and environmental reasons, it is desirable to utilize plant materials or biomass that are typically considered waste. For example, suitable biomass includes non-grain soybean plant parts (e.g., leaves, husks and stems), soybean kernels, citrus fruit peels (e.g., oranges, lemons, limes, etc.), banana peels, tea leaves, corn stover, corn kernels, corn kernel distillates, coconut shells, and combinations thereof. In one embodiment, the plant-based material / biomass is a non-grain soybean plant part selected from the group consisting of husks, stalks, leaves, and combinations thereof. Although many of the examples described in this disclosure and within this application relate to such soybean plant material embodiments, this should not be construed as a limitation unless expressly indicated. Instead, unless expressly indicated, the teachings within this application are applicable to other types of plant-based materials as well.
[0011] Typically, the plant-based material is subjected to mechanical manipulation, such as cutting, chopping, pulverizing, grinding, etc., and optionally rinsed and dried such that the plant-based material is a dry powder or particles.
[0012] Without wishing to be bound by any particular theory, it is believed that the composition of these plant-based materials plays a role in the unique and desirable properties of the activated carbon particles of the present invention. Without wishing to be bound by any particular theory, it is believed that the proteins within the materials result in activated carbon particles that contain nitrogen atoms, at least some of which are electrically conductive graphitic phases or sp of G-band carbon. 2 It is believed to replace carbon atoms in the crystal lattice structure of a hybrid graphitic phase.
[0013] B. Heat Pretreatment The method of producing activated carbon particles of the activated carbon powder may optionally include a thermal pretreatment of a plant material powder comprising particles of clean, dried plant material, by heating the plant material powder under an inert pretreatment atmosphere at a pretreatment temperature and for a pretreatment time sufficient to release volatile, less stable molecules within the plant material powder to produce a partially carbonized plant material powder suitable for an activated pyrolysis process as described below.
[0014] In one embodiment, the pretreatment inert atmosphere is selected from the group consisting of nitrogen, argon, and combinations thereof, the pretreatment temperature is in the range of about 250°C to about 500°C, and the pretreatment time is in the range of about 1 hour to about 2 hours.
[0015] In another embodiment, the pretreatment inert atmosphere is selected from the group consisting of nitrogen, argon, and combinations thereof, the pretreatment temperature is in the range of about 300° C. to about 400° C., and the pretreatment time is in the range of about 1 hour to about 2 hours.
[0016] If thermal pretreatment is performed, such a method may be referred to herein as a "two-stage" or "two-stage" method. If thermal pretreatment is not performed, such a method may be referred to herein as a "one-stage" or "single-stage" method. Surprisingly, not performing any thermal pretreatment significantly reduces processing time and cost without significantly decreasing the charge storage capacity of the resulting material. In fact, some results to date have shown that the one-stage solution can actually increase the charge storage capacity. For example, the current-voltage characteristics of the two-stage and one-stage carbons shown in Figures 18 and 19 are similar. On the other hand, the larger area under the CV curve for the one-stage carbon compared to the two-stage carbon shown in Figures 18 and 19 suggests that the one-stage carbon had improved charge storage capacity. Unless explicitly stated, the properties of the activated carbon powders shown within this application apply to powders produced by either the one-stage or two-stage methods.
[0017] C. Activated pyrolysis treatment The method includes subjecting a precursor material, including uncarbonized plant material powder, partially carbonized plant material powder (which may have been subjected to a thermal pretreatment as described above), or a combination thereof, to an activated pyrolysis process, which carbonizes the precursor material and contributes high surface area, modified meso- and microporosity, modified composition, and modified crystallographic structure. For the avoidance of confusion, in the case of partially carbonized plant material powder, the activated pyrolysis process continues the carbonization of the partially carbonized plant material powder.
[0018] 1. Mixing the precursor and activator The activation pyrolysis process includes mixing the precursor with an activator to form a precursor-activator mixture. The activator is selected to react with carbon in the precursor during the activation pyrolysis process to form one or more products suitable for removal during a cleaning process performed after the activation pyrolysis process. In one embodiment, the activator is selected from the group consisting of KOH, NaOH, ZnCl2, H3PO4, steam, and combinations thereof. In another embodiment, the activator is KOH.
[0019] An important factor in controlling one or more of the properties of the resulting activated carbon particles is the selection of the activator and the relative amounts of activator and precursor in the mixture. It has been observed that KOH tends to be the most reactive or efficient of the activators mentioned above. Furthermore, it has been observed that increasing the amount of activator relative to the precursor tends to increase the surface area of the resulting activated carbon particles.
[0020] Mesopores in activated carbon particles (i.e., 2 nm to 50 It was also observed that the relative amount of pores (i.e., pores with diameters in the nm range) and micropores (i.e., pores with diameters less than 2 nm) was affected by the amount of activator relative to the precursor. Specifically, it was observed that as the relative amount of activator increased, the average pore size tended to decrease. This observation at first glance seems counterintuitive, since an increase in the amount of activator would be expected to increase the pore size. Without being bound to a particular theory, it is believed that the decrease in average pore size may be the result of the pores collapsing when they reach a large enough size.
[0021] Additionally, it has been observed that as the relative amount of activator increases, the nitrogen content of the activated carbon particles tends to decrease (discussed in more detail below).
[0022] Additionally, it has been observed that as the relative amount of activator increases, the crystallographic structure of the activated carbon particles tends to become less uniform (as discussed in more detail below). Without wishing to be bound by theory, it is believed that nitrogen atoms (which replace carbon atoms in the graphitic phase of carbon or G-band carbon within the activated carbon particles, sometimes referred to as "graphitic nitrogen") are lost as part of the activation process, causing the crystallographic structure of the graphitic phase or G-band carbon to become less uniform, and as a result, as the relative amount of activator increases, the activated carbon tends to contain less G-band carbon relative to the diamond phase or D-band carbon.
[0023] In one embodiment, the precursor and non-vapor activator are in a mass ratio ranging from about 1:0.5 to about 1:3.
[0024] In another embodiment, the precursor and non-vapor activator are in a mass ratio ranging from about 1:1 to about 1:2.
[0025] In other embodiments, the precursor and non-vapor activator are in a mass ratio ranging from about 1:0.125 to about 1:1.
[0026] 2. Pyrolysis of the precursor-activator mixture The activated pyrolysis process further includes heating the mixture of precursor and activator under an inert pyrolysis atmosphere at a pyrolysis temperature and for a pyrolysis time sufficient to complete carbonization of the precursor to form an activated pyrolysis material.
[0027] In one embodiment, the pyrolysis atmosphere is selected from the group consisting of nitrogen, argon and combinations thereof, the pyrolysis temperature is in the range of about 600°C to about 900°C, and the pyrolysis time is in the range of about 1 hour to about 2 hours.
[0028] In another embodiment, the pyrolysis atmosphere is selected from the group consisting of nitrogen, argon and combinations thereof, the pyrolysis temperature is in the range of about 700° C. to about 850° C., and the pyrolysis time is in the range of about 1 hour to about 2 hours.
[0029] D. Cleaning Treatment The method further includes subjecting the activated pyrolyzed material to a washing process that includes contacting the activated pyrolyzed material with one or more washing fluids suitable for reducing or removing one or more products of the reaction between the carbon and the activating agent from the activated pyrolyzed material to form activated carbon particles of the activated carbon powder.
[0030] In one embodiment, at least one of the cleaning solutions of the cleaning process is a solution containing a dissolved compound selected from the group consisting of HCl, DI water, and combinations thereof.
[0031] In another embodiment, at least one of the cleaning solutions of the cleaning process is a solution comprising an HCl solution and deionized water, wherein the next cleaning solution is deionized water.
[0032] E. Drying The method may further include drying the activated carbon particles. Also, if the activated carbon particles are agglomerated, they can be subjected to physical manipulation (e.g., grinding) to better separate them.
[0033] III. Activated carbon particles A. High surface area As discussed above, the activated carbon particles of the present invention have certain properties that make them well suited for electrical energy storage applications, such as electrodes for batteries and supercapacitors. One such property is a relatively high surface area. For example, in one embodiment, the activated carbon particles have a surface area of about 1,100 m. 2 / g ~ approx. 2,100m 2 / g. In another embodiment, the BET surface area of the activated carbon particles is in the range of about 900 m 2 / g ~ approx. 2,500m 2 In yet another embodiment, the BET surface area of the activated carbon particles is in the range of about 1,300 m 2 / g ~ approx. 2,100m 2 / g range.
[0034] As noted above, the degree of surface area can be controlled primarily by the selection of activator and the relative amount of carbon precursor to the material. Specifically, selecting a more effective activator and / or more activator relative to the precursor tends to result in a higher surface area.
[0035] B. Carbon containing D-band and G-band materials The activated carbon particles include carbon, which has different crystallographic structures. 3 D-band carbon, which corresponds to a hybrid disordered carbon phase, and sp 2 and G-band carbon corresponding to a hybrid graphite phase.
[0036] In one embodiment, the D band carbon and the G band carbon are identified using Raman spectroscopy to determine the D band carbon (I D ) and G-band carbon (I G ) is the relative strength of I G / I D The ratio reached is in the range of 0 to about 2.
[0037] In another embodiment, I G / I D The ratio ranges from about 0 to about 1.7.
[0038] In yet another embodiment, I G / I D The ratio ranges from about 0 to about 1.5.
[0039] The presence of the G phase is predicted to improve the charge storage capacity of the activated carbon due to its higher conductivity than that of D phase carbon.
[0040] C. Nitrogen As mentioned above, the activated carbon particles also contain nitrogen. At least some of the nitrogen atoms are in the sp 2 It is believed that nitrogen substitutes for carbon atoms in the crystal lattice structure of the hybrid graphite phase. As mentioned above, the nitrogen content of the activated carbon particles can be controlled or selected through the activation pyrolysis process. In particular, it is observed that the mass ratio of the precursor to the activator plays a substantial role in the nitrogen content. Without being bound to a particular theory, it is believed that nitrogen can be leached or removed from the activated carbon through pores that are formed as part of the activation reaction between the activator and the precursor.
[0041] It has been observed that desirable performance of the activated carbon particles in electrical storage applications, such as in electrodes of batteries and supercapacitors, is achieved by controlling the nitrogen content of the activated carbon particles such that the nitrogen is in an amount ranging from about 0.5 atomic % to about 1.7 atomic % of the activated carbon particles, as determined by X-ray photoelectron spectroscopy.
[0042] In other embodiments, the amount of nitrogen ranges from about 0.4 atomic % to about 1.8 atomic % of the activated carbon particles.
[0043] In yet another embodiment, the amount of nitrogen ranges from about 0.5 atomic % to about 1.1 atomic % of the activated carbon particles.
[0044] D. Pore As mentioned above, activated carbon particles are 2 nm to 50 This includes mesopores, which have diameters in the nm range, and micropores, which have diameters less than 2 nm. 2 / g ~ approx. 2,500m 2 In addition to the surface area, which is in the range of 0.1 μm / g, the porosity of the activated carbon particles of the present invention can be characterized by a variety of methods (see, for example, Table A below).
[0045] 1. Average pore width For example, activated carbon particles can be characterized in terms of average pore width, which is a measure of the relative amount of mesopores and micropores. In one embodiment, the average pore width of the adsorption as determined by the Barrett-Joyner-Halenda (BJH) method ranges from about 1 nm to about 4 nm. In another embodiment, the average pore width ranges from about 1 nm to about 2 nm. In yet another embodiment, the average pore width ranges from about 2 nm to about 4 nm.
[0046] The ability to tune the pore size allows for the use of a wide range of electrolytes: appropriately sized pores allow easy access for the electrolyte ions within the pores of the carbon.
[0047] 2. Micropore surface area The activated carbon particles of the present invention can also be characterized in terms of micropore surface area. For example, in one embodiment, the micropore surface area as determined by the t-plot method is about 300 m 2 / g ~ approx. 1,300m 2 / g. In another embodiment, the micropore surface area is in the range of about 1,000 m 2 / g ~ approx. 1,300m 2 In yet another embodiment, the micropore surface area is in the range of about 600 m 2 / g ~ approx. 1,200m 2 / g range.
[0048] The presence of micropores tends to provide a larger surface area for the adsorption and desorption process of electrolyte ions.
[0049] 3. Micropore volume The activated carbon particles can also be characterized in terms of micropore volume. For example, in one embodiment, the micropore volume as determined by the t-plot method is about 0.1 cm 3 / g ~ approx. 0.7cm 3 / g. In another embodiment, the micropore volume is about 0.4 cm 3 / g ~ approx. 0.7cm 3 / g range.
[0050] It is believed that the micropore volume can be controlled to enhance the charge storage capacity of the activated carbon.
[0051] 4. Cumulative surface of micropores of a particular size Activated carbon particles can also be characterized in terms of the cumulative surface area of micropores in a particular size range. For example, in one embodiment, activated carbon particles have a cumulative surface area of micropores having a hydraulic radius in the range of 0.285 nm to 1.30 nm of about 1,000 m 2 / g ~ approx. 3,000m 2 In another embodiment, the cumulative surface area of micropores having a hydraulic radius in the range of 0.285 nm to 1.30 nm is in the range of about 1,400 m 2 / g ~ approx. 2,600m 2 In yet another embodiment, the cumulative surface area of micropores having a hydraulic radius in the range of 0.285 nm to 1.30 nm is in the range of about 1,700 m 2 / g ~ approx. 2,700m 2 / g range.
[0052] It has been observed that the cumulative surface area of micropores with hydraulic radii in the range of 0.285 nm to 1.30 nm affects the charge storage capacity of carbon. For example, the cumulative surface area of micropores with hydraulic radii in the range of 0.285 nm to 1.30 nm is 2,000 to 2,600 m 2 / g range is believed to allow easier access of the electrolyte within the pores, thus resulting in higher charge storage capacity.
[0053] 5. Cumulative volume of micropores of a particular size Activated carbon particles can also be characterized in terms of the cumulative volume of micropores in a particular size range. For example, in one embodiment, the cumulative volume of micropores having a hydraulic radius in the range of 0.285 nm to 1.30 nm is about 0.35 cm. 3 / g ~ approx. 1.6cm 3 In another embodiment, the cumulative volume of micropores having a hydraulic radius in the range of 0.285 nm to 1.30 nm is about 0.6 cm3 / g ~ approx. 1.1cm 3 In yet another embodiment, the cumulative volume of micropores having a hydraulic radius in the range of 0.285 nm to 1.30 nm is in the range of 0.4 cm 3 / g ~ approx. 1.4cm 3 / g range.
[0054] The cumulative volume and surface area of the micropores are alternative means of quantifying the degree of porosity within the abovementioned pore size ranges.
[0055] E. Specific capacitance of activated carbon particles The activated carbon particles are particularly well suited for use as electrode materials in energy storage applications, such as batteries and supercapacitors. Their suitability for such applications is determined by their specific capacitance (C sp ) can be evaluated from the perspective of
[0056] In one embodiment, the activated carbon particles produced using the two-step process have a specific capacitance at a current density of 1 Ampere / gram (A / g) ranging from about 130 Farads / gram (F / g) to about 330 F / g. In another embodiment, the specific capacitance at a current density of 1 A / g ranges from about 160 F / g to about 210 F / g. In yet another embodiment, the specific capacitance at a current density of 1 A / g ranges from about 110 F / g to about 260 F / g.
[0057] In one embodiment, the activated carbon particles produced using the one-step process have a specific capacitance at a current density of 1 Ampere / gram (A / g) ranging from about 100 F / g to about 250 F / g, at a current density of 5 Amperes / gram (A / g) the specific capacitance ranges from about 80 Farads / gram (F / g) to about 175 F / g, and at a current density of 10 Amperes / gram (A / g) the specific capacitance ranges from about 60 Farads / gram (F / g) to about 160 F / g.
[0058] IV. Energy Storage Devices The activated carbon particles of the present invention were tested in an energy storage device, and the activated carbon particles contributed to the device having high rate stability.
[0059] For example, when the discharge current was increased from 3 A / g to 15 A / g, the electrode formed from the two-stage activated carbon particles retained more than 80% of its initial charge storage capacity. Moreover, the supercapacitor device fabricated using those two-stage carbon particles retained more than 95% of its initial charge storage capacity and had a coulombic efficiency of nearly 100% over more than 5,000 charge-discharge cycles.
[0060] For example, when the discharge current was increased from 1 A / g to 5 A / g, the electrode formed from the single-stage activated carbon particles retained about 78.5% of its initial charge storage capacity. When the discharge current was further increased from 5 A / g to 10 A / g, only an additional 4.5% charge capacity loss was observed (i.e., retaining about 74% of its initial charge storage capacity) (shown in FIG. 22). Moreover, the supercapacitor device fabricated using those single-stage carbon particles retained more than 90% of its initial charge storage capacity and had a coulombic efficiency of nearly 100% over a charge-discharge study of over 10,000 cycles (see FIG. 24(A)). EXAMPLES
[0061] V. Working Examples A. Synthesis Activated carbon samples were synthesized from soybean leaves, stems and husks. The soybean material was washed and dried at 60°C. The dried material was crushed into a fine powder. This powder served as the precursor for the samples produced using the one-step method. For the samples produced using the two-step method, the powder was subjected to thermal pretreatment at 350°C for 2 hours under nitrogen atmosphere to release volatile, less stable molecules in the plant material powder, producing a partially carbonized plant powder, which was a suitable precursor for activation and pyrolysis.
[0062] An activation pyrolysis of the precursor was carried out. The activation pyrolysis included mixing the precursor with a KOH activator to form a precursor-activator mixture. The KOH reacted with carbon in the precursor during the activation pyrolysis to form one or more products suitable for removal during a cleaning process carried out after the activation pyrolysis. In particular, at least one product represented by formula (1): 6KOH+2C(from precursor) → 2K+3H2+2K2CO3(1) The following reaction is thought to occur:
[0063] Various mass ratios of precursor:activator (e.g., 1:0.125, 1:0.25, 1:0.5, 1:1, 1:2, and 1:3) were selected to evaluate the effect (e.g., on surface area) of the resulting activated carbon. For example, 1 gram of precursor was mixed with 1 gram of KOH pellets to achieve a 1:1 mass ratio. A sample not mixed with KOH activator was used as a control.
[0064] The mixture of precursor and activator was then heated under an inert pyrolysis atmosphere of nitrogen (under nitrogen flow in a tube furnace) at a pyrolysis temperature of about 800° C. for a pyrolysis time of about 2 hours, which was sufficient to complete the carbonization of the precursor to form an activated pyrolyzed material.
[0065] The activated pyrolysis material was then ground into a powder and subjected to a washing treatment with one or more washing solutions suitable for reducing or removing one or more products of the reaction between the carbon and the activator, in this case potassium carbonate. In particular, the material was washed with a 1M HCl aqueous washing solution, followed by washing with deionized water. The hydrochloric acid reacted with the potassium carbonate to form carbon dioxide gas, which was released, and the solute potassium chloride was removed with deionized water. The activated carbon particles were dried overnight at 60°C.
[0066] 1. Specific Capacitance As shown in FIG. 1, carbon from soybean leaves has a substantially higher specific capacitance than commercial carbons used for batteries and supercapacitors. Carbon from soybean leaves had a much higher energy storage capacity than commercial carbons. For example, at 10 A / g, the commercial carbon stored 16 F / g, while carbon from soybean leaves stored 121 F / g, more than 7.5 times the energy storage capacity. In addition, carbon from soybean leaves exhibits more stable rate characteristics. For example, when the discharge current density was increased from 3 A / g to 15 A / g, the commercial carbon only retained 16.3% of its initial charge storage capacity, while carbon from soybean leaves retained 83.1% of its initial charge storage capacity.
[0067] 2. X-ray diffraction The synthesized carbon samples were analyzed by powder X-ray diffraction (Shimadzu X-ray diffractometer) using 2θ-θ scan and CuK as the radiation source. α1 (λ=1.5406 Å). Figures 2, 9, and 10 show the XRD patterns of unactivated carbon and carbon activated with various mass ratios of KOH from leaves, shells, and stems. In the activated carbon samples, the XRD peaks centered around 2θ of 24° and 44° correspond to the (002) and (100) planes of graphitic carbon. The presence of graphitic phase indicates suitability as an electrode material. The broad and low intensity peaks indicate the disordered nature of the carbon samples. In general, with increasing mass ratio of KOH, the peaks of graphitic carbon tend to become broader and less intense, suggesting a reduction in the graphitic structure in the carbon samples. These observations reveal that the degree of graphitization of the carbon samples is mainly a function of chemical activation.
[0068] 3. Raman spectroscopy Argon ion laser Raman spectroscopy was used to identify the G and D bands of carbon using a wavelength of 514.5 nm as the excitation source. As shown in Figures 5-7, Raman spectroscopy was used to identify the graphite and diamond phases of carbon produced from soybean husks, stems and leaves, respectively. Peaks at 1354 and 1591 cm were observed in all samples. -1 Two characteristic peaks around 0.01 are observed, which can be assigned to the D and G bands of carbon, respectively. The presence of the graphitic phase is advantageous because this is the conducting phase of carbon.
[0069] 4. Nitrogen adsorption / desorption isotherm The surface area of the samples was measured using nitrogen adsorption-desorption isotherms, which were carried out using an ASAP 2020 volumetric adsorption analyzer (Micrometrics, USA) at 77 K. Prior to analysis, the samples were degassed for 24 h at 90 °C to remove any gas adsorbed on the surface and within the pores of the carbon.
[0070] Nitrogen adsorption / desorption isotherms for activated and unactivated soybean leaves, husks, and stems are shown in Figures 3, 11, and 12. It is clear that the pore size and specific surface area of the activated carbon were affected by the mass ratio of soybean material:activator. In general, there is a tendency for the surface area to increase as the relative amount of activator increases. For example, the surface area of husk carbon increased by 1 m2 after activation with KOH. 2 / g to 2005m 2 / g. Shell / stalk samples activated using higher amounts of KOH exhibited Type I isotherms with most N2 adsorption at relative pressures (P / P0) below 0.35 and nearly parallel slopes of the isotherms (with respect to the x-axis) above P / P0 of 0.35, which are typical of micropores in the carbon. On the other hand, activation using lower amounts of KOH exhibited combined Type I and IV isotherms with discernible hysteresis loops above P / P0 of 0.5, indicating the presence of both micropore and mesopore structures. In contrast, the very low N2 adsorption of the unactivated samples indicates the near absence of porous structure.
[0071] 5. BJH Pore Distribution These observations were further confirmed by the plots of BJT pore size distribution shown in Figures 4, 13, and 14. The pore sizes of carbons derived from soybean leaves, husks, and stalks are centered around 2 nm.
[0072] 6. Scanning Electron Microscopy The micropore structure and morphology of all samples were evaluated using field emission scanning electron microscopy. The scanning electron microscopy (SEM) images are shown in Figure 8. From the SEM images, it is evident that KOH activation modified the surface of the carbon derived from soy materials. The high porosity of soy-derived carbon provides a higher surface area for electrolyte ions, which tends to increase the charge storage capacity.
[0073] The pore and surface area characteristics of activated carbon from soybean leaves, husks and stalks are shown in Table A below.
[0074] [Table 1]
[0075] As can be seen, these carbons exhibit the presence of micropores and mesopores, which is beneficial for activated carbon-based materials used in energy storage materials. The presence of micropores provides a larger surface area for the adsorption and desorption process of electrolyte ions. The presence of mesopores ensures the accessibility of the surface area and provides wider channels for several electrolyte ions to diffuse simultaneously without experiencing geometrical resistance. These aspects are believed to make the activated carbon material of the present invention suitable for use with various electrolytes. Thus, the material can be used in the manufacture of supercapacitors or batteries, such as lithium-ion, sodium-ion and potassium-ion batteries / supercapacitors.
[0076] 7. Effect of electrolytes The electrochemical properties of SB-2 (selected as a representative material) in various electrolytes were further investigated. Alkaline (KOH and LiOH), acid (H2SO4) and salt (Na2SO4) solutions were used for this study. Figure 15 shows the change in specific capacitance in various electrolytes as a function of applied current density.
[0077] 8. Effect of nitrogen doping Urea was used to dope the commercial carbon with nitrogen. For this, a 1:2 ratio of commercial carbon and urea (200 mg commercial carbon and 400 mg urea) was dissolved in 5 ml of DI water. The solution was sonicated in an ultrasonic bath for 2 hours, and then the mixture was dried on a hot plate at 85 °C. The dried powder was carbonized under nitrogen at 800 °C (5 °C / min) for 2 hours. After natural cooling to room temperature, the powder was washed with DI water. The washed powder was dried overnight in a conventional oven at 65 °C. The charge-discharge profiles of the commercial carbon and the nitrogen-doped commercial carbon are shown in Figure 16. As can be seen in Figure 16, nitrogen doping did not improve the energy storage capacity of the commercial carbon. Although the doping method may not be effective, this test indicates that the properties achieved by the materials of the claimed invention are at least in part due to the sp of G-band carbon. 2 This is believed to be due to the presence of nitrogen atoms from the biomass substituting for carbon atoms in the crystal lattice structure of the hybrid graphitic phase nitrogen.
[0078] 9. Capacitance retention and coulombic efficiency testing Referring to Figure 17, the two-stage activated carbon material of the present invention was used as an electrode material to form a coin cell supercapacitor. As shown in Figure 17, the performance of the supercapacitor was very similar to that of an ideal capacitor. The device underwent over 8,000 charge-discharge cycles, with very stable performance and nearly 100% coulombic efficiency.
[0079] Referring to Figure 24(A), the two-stage activated carbon material of the present invention was used as an electrode material to form a coin cell supercapacitor. As shown in Figure 24(A), the device underwent over 10,000 charge-discharge cycles with very stable performance, retaining more than 90% of its initial charge storage and with a coulombic efficiency of nearly 100%.
[0080] VI. Conclusion Having illustrated and described the principles of this invention, it will be apparent to those skilled in the art that the invention can be changed in arrangement and detail without departing from such principles.
[0081] While the materials and methods of the present invention have been described with reference to various embodiments and illustrative examples, it will be apparent to those skilled in the art that changes may be made to the materials and methods described herein without departing from the concept, spirit and scope of the invention. All such similar substitutes and modifications apparent to those skilled in the art are deemed to be within the spirit, scope and concept of the invention as defined by the appended claims.
Claims
1. Activated carbon powder comprising activated carbon particles, the activated carbon particles having a diameter of about 1100 mm. 2 / g ~ approx. 2,500m 2 / g, and the activated carbon particles have a Brunauer-Emmett-Teller (BET) surface area in the range of (a) Below: (i) sp 3 D-band carbon, which corresponds to a hybrid disordered carbon phase; and (ii) sp 2 G-band carbon corresponding to a hybrid graphite phase Including carbon, Here, the D band carbon and the G band carbon are identified using Raman spectroscopy, and the D band carbon (I D ) and G-band carbon (I G ) is expressed as I G / I D The ratio is in the range of 0 to about 2. (b) nitrogen in an amount ranging from about 0.3 atomic % to about 1.8 atomic % of the activated carbon particles, as determined by X-ray photoelectron spectroscopy; Here, at least some of the nitrogen atoms are sp 2 Substituting carbon atoms in the crystal lattice structure of the hybrid graphite phase, (c) mesopores having a diameter ranging from 2 nm to 50 nm and micropores having a diameter of less than 2 nm The activated carbon particles include (i) an average pore width as determined by the Barrett-Joyner-Halenda (BJH) method: in the range of about 1 nm to about 4 nm; (ii) Micropore surface area as determined by t-plot method: about 300 m 2 / g ~ approx. 1,350m 2 / g range, and (iii) Cumulative surface area of micropores having a hydraulic radius in the range of 0.285 nm to 1.30 nm: about 1,000 m 2 / g ~ approx. 3,000m 2 / g range wherein the activated carbon particles are obtained by activating pyrolysis of a nitrogen source plant material powder, the plant material powder being derived from a non-grain soybean plant part.
2. The BET surface area of the activated carbon particles is about 1,300 m 2 / g ~ approx. 2,200m 2 / g, I G / I D The ratio ranges from about 0 to about 1.5; the amount of nitrogen ranges from about 0.4 atomic % to about 1.8 atomic % of the activated carbon particles; The micropore surface area, as determined by t-plot method, is about 600 m 2 / g ~ approx. 1,200m 2 / g, or The cumulative surface area of micropores having a hydraulic radius in the range of 0.285 nm to 1.30 nm is approximately 1,400 m 2 / g ~ approx. 2,600m 2 / g, 2. The activated carbon powder of claim 1.
3. 2. The activated carbon powder of claim 1, wherein the average pore width as determined by the BJH method is in the range of about 2 nm to about 4 nm, or in the range of about 1 nm to about 2 nm.
4. The activated carbon particles have a specific capacitance (C) in a range selected from the group consisting of about 130 F / g to about 330 F / g, about 160 F / g to about 210 F / g, about 110 F / g to about 260 F / g, and about 100 F / g to about 250 F / g at a current density of 1 A / g. sp 2. The activated carbon powder of claim 1 having a molecular weight of 1.0 or more.
5. A method for producing activated carbon particles of the activated carbon powder according to any one of claims 1 to 4, comprising the steps of: performing an activated pyrolysis treatment of a precursor comprising powder of uncarbonized plant material, powder of partially carbonized plant material, or a combination thereof; wherein the powdered plant material is a nitrogen source within the activated carbon particles, the powdered plant material is derived from non-grain soybean plant parts, and the activated pyrolysis process comprises: - mixing said precursor with an activator to form a precursor-activator mixture; wherein the activating agent is selected to react with carbon in the precursor during the activation pyrolysis process to form one or more products suitable for removal during a cleaning process carried out after the activation pyrolysis process, and the activating agent is selected from KOH, NaOH, ZnCl 2 , H 3 P.O. 4 , steam, and combinations thereof, wherein the precursor and the activator are in a mass ratio ranging from 1:0.5 to 1:3; and forming an activated pyrolyzed material by heating the mixture of precursor and activator under an inert pyrolysis atmosphere at a pyrolysis temperature and for a pyrolysis time sufficient to complete carbonization of the precursor, wherein the pyrolysis atmosphere is selected from the group consisting of nitrogen, argon and combinations thereof, the pyrolysis temperature is in the range of 600°C to 900°C, and the pyrolysis time is in the range of 1 hour to 2 hours; and, performing a washing treatment of the activated pyrolysis material with one or more washing liquids suitable for reducing or removing from the activated pyrolysis material one or more products of a reaction between carbon and an activating agent to form activated carbon particles of an activated carbon powder, wherein at least one of the washing liquids of the washing treatment is a solution comprising an HCl solution and deionized water, wherein a subsequent washing liquid is deionized water, and the method includes drying the activated carbon particles.
6. 6. The method of claim 5, further comprising performing a thermal pretreatment prior to the activated pyrolysis treatment, wherein the thermal pretreatment comprises heating uncarbonized plant material powder under an inert pretreatment atmosphere at a pretreatment temperature and for a pretreatment time sufficient to release volatile, less stable molecules in the uncarbonized plant material powder to produce a partially carbonized plant material powder suitable for activated pyrolysis treatment.
7. 6. The method of claim 5, wherein the precursor comprises uncarbonized powdered plant material, or the precursor comprises partially carbonized powdered plant material.
8. the pretreatment inert atmosphere is selected from the group consisting of nitrogen, argon, and combinations thereof; the pretreatment temperature is in the range of about 250° C. to about 500° C.; and The pretreatment time ranges from about 1 hour to about 2 hours. The method according to claim 6.
9. the mass ratio of the precursor to the activator is in the range of 1:1 to 1:2; the pyrolysis atmosphere is selected from the group consisting of nitrogen, argon, and combinations thereof; The pyrolysis temperature is in the range of 700°C to 850°C, and The pyrolysis time is in the range of 1 hour to 2 hours; The method according to claim 5.
10. 5. An electrode comprising the activated carbon powder according to claim 1.
11. A battery comprising the electrode of claim 10.
12. A supercapacitor comprising the electrode of claim 10.
Citation Information
Patent Citations
Electrode for electric double layer capacitor, method of manufacturing same, and electrode for electric double layer capacitor using same
JP2010135647A
Activated carbon material for high-energy-density ultracapacitors
JP2012512129A
Carbon material for capacitor and capacitor
JP2017147338A